Evaluasi Program Literasi Keagamaan Siswa Menggunakan Model CIPP (Context, Input, Process and Product) di SMPN 2 Koto Baru Dharmasraya - Melisa, Tiara; I, Iswantir (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The background This research comes from reading and writing is an activity that is no longer foreign to the public. By reading, people's thinking skills will continue to be honed and grow, knowledge of insight will also increase or increase the quality of the main source of people's energy in this world. Therefore, reading becomes a desire for people to be able to compete with other nations in the world. Indonesian people themselves are still lacking in attention to reading and writing. Based on that, the author was interested in studying this in the student faith literacy program at SMPN 2 Koto Terkini which found different appreciation from others. As a result, researchers conducted an evaluation both in terms of shortcomings and advantages. This research intends to describe the results of implementing the faith literacy program at SMPN 2 Koto Terkini using the CIPP model developed by Daniel Suffbeam. Based on that, the question arises how to assess the student faith literacy program using the CIPP model